Rotatinuous stocking : an innovation in grazing management based on animal behaviour and implications to pasture production, foraging behaviour, herbage intake and methane emission by grazing sheep - Savian, Jean Victor (2017)
The aim of this thesis was to investigate contrasting pasture management strategies on the foraging behaviour, pasture production, carcass characteristics, herbage intake, faecal gas emissions and methane emission by sheep grazing Italian ryegrass (Lolium multiflorum) pastures. The experiment was carried out in 2014 and 2015. The experimental design was a randomized complete block with four replicates and two grazing strategy treatments (traditional rotational stocking method – RT meaning pre- and post-grazing target heights of 25 and 5 cm, respectively and, “rotatinuous stocking” – RN with pre- and post-grazing target heights of 18 and 11 cm, respectively). The grazing management was based on a 1-day strip-grazing regime. Male castrated sheep were used. The actual average sward heights for the RN treatment were 17.9 and 11.1 cm (pre- and post-grazing, respectively) and 27.1 and 7.8 cm for the RT (pre- and post-grazing, respectively). The stocking period in 2014 was 146 and 140 days (RN and RT, respectively) and in 2015 it was 155 and 146 days (RN and RT, respectively). The diurnal animal activities (grazing, ruminating and resting time) did not differ between treatments, with average of 439.6, 166.9 and 85.0 minutes, respectively. The bite rate, feeding station per min and steps per min were greater at the RN than the RT treatment. Grazing time and bite rate were greater in the afternoon than morning in both treatments. Therefore, the daily herbage intake by sheep grazing Italian ryegrass was greater for the RN than the RT treatment (CHAPTER II). The herbage production in the RN was 28% higher than the RT treatment. Individual average daily gain and live weight gain per hectare were greater in the RN than the RT treatment (CHAPTER III). RN treatment presented greater final live weight, carcass and commercial cut weights from grazing sheep than RT treatment (CHAPTER IV). RN treatment had a faecal chemical quality greater than RT treatment, resulting in a greater daily nitrogen excretion per animal and greater faecal CH4 and N2O emissions (CHAPTER VI). The “rotatinuous stocking” (RN) was the better grazing management strategy for mitigation of CH4 emissions by sheep grazing Italian ryegrass, emitting 64% less CH4 per unit area and 170% less CH4 per unit of animal product than the traditional rotational stocking method (RT) (CHAPTER V).